2020
DOI: 10.3390/jcm9020447
|View full text |Cite
|
Sign up to set email alerts
|

Combined Brain-Heart Magnetic Resonance Imaging in Autoimmune Rheumatic Disease Patients with Cardiac Symptoms: Hypothesis Generating Insights from a Cross-Sectional Study

Abstract: Background: Autoimmune rheumatic diseases (ARDs) may affect both the heart and the brain. However, little is known about the interaction between these organs in ARD patients. We asked whether brain lesions are more frequent in ARD patients with cardiac symptoms compared with non-ARD patients with cardiovascular disease (CVD). Methods: 57 ARD patients with mean age of 48 ± 13 years presenting with shortness of breath, chest pain, and/or palpitations, and 30 age-matched disease-controls with non-autoimmune CVD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…At the moment, there is no data supporting a combined brain/heart evaluation in HF, except one study in autoimmune rheumatic diseases with cardiac symptoms, published by our group [ 56 ]. However, it has been documented that HF patients exhibit CD of attention and memory, and medial temporal lobe atrophy (MTA) seems to be responsible [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, there is no data supporting a combined brain/heart evaluation in HF, except one study in autoimmune rheumatic diseases with cardiac symptoms, published by our group [ 56 ]. However, it has been documented that HF patients exhibit CD of attention and memory, and medial temporal lobe atrophy (MTA) seems to be responsible [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is evidence that cerebral MRI can detect vascular and inflammatory lesions in IRD [ 59 , 60 ]. Markousis-Mavrogenis et al observed that subclinical CNS involvement was frequent in IRD patients with cardiac symptoms and cardiac involvement [ 61 ]. Consequently, MRT is the optimal technique for the simultaneous detection of cerebral and cardiac inflammatory involvement in IRD [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…2). T2-mapping is performed on 3 corresponding LV short-axis slices using a black-blood prepared, navigator-gated, free-breathing hybrid gradient (echo planar imaging) and spinecho multiecho sequence [67]. Finally, T2 mapping can identify a specific group of hypertensions with myocardial edema [40].…”
Section: Heart and Kidney Interactionmentioning
confidence: 99%
“…A standard MRI protocol for brain evaluation should include the following measurements [67]: a) Spin-echo T1-and T2-weighted imaging where only fat is bright, while in T2 imaging both fat and water are bright. FLAIR imaging is also similar to T2 and can be used to identify subtle oedema after a stroke (▶Fig.…”
Section: Heart and Kidney Interactionmentioning
confidence: 99%